UJI DAYA TERIMA DAN KANDUNGAN GIZI BISKUIT DENGAN PENAMBAHAN TEPUNG IKAN LELE DUMBO (Clarias gariepinus ) DAN DAUN BANGUN BANGUN (Coleus amboinicus Lour) - Devy Andriana Sardiana; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT Dumbo catfish (Clarias gariepinus) and bangun bangun leaf (Coleus ambonicus Lour) can be processed into biscuit. Biscuit is one of additional food that can full fill the needs of people nutrient. Biscuits had sweet taste and interesting shape. This research purpose to determine the acceptability test and nutritional content of biscuits with the addition of dumbo catfish and bangun bangun leaf. The type of research was an experiment conducted by completely randomized design using two factors and with two treatments, the treatmens are the addition of dumbo catfish and bangun bangun leaf with treatments 10% : 20%, and 15% : 20%. The acceptability biscuit with the addition of dumbo catfish and bangun bangun leaf by FKM USU students as much as 30 people, nutrient analysis was tested in laboratory of industrial research and standarization Agency Medan. The results organoleptic test based on color, aroma, flavor, and texture biscuit by thirty students panelist showed the most preferred are biscuit mixture of dumbo catfish 15% and bangun bangun leaf 20%. Acceptability of students showed that two treatments have been preferred by people. The result of nutrional content analysis showed that two treatments has content of carbohydrates 54,8g, 55,3 g, content of protein 10,2g 11,3g content fat 21,6g 20,9g, content of calcium 397mmg, 362mmg and phosphor 327,6 mmg and 389,4 mmg. It is recommended for people to take of dumbo catfish and bangun bangun leaf biscuit as alternative additional food for people.As well as the need to do further research to see the content of nutrients contained in dumbo catfish and bangun bangun leaf biscuit. Keywords :Dumbo catfish, Bangun bangun leaf, Biscuit, Acceptability, Nutrient content